A retrospective case study of the thematic content of psychotic experiences in a first episode psychosis population. (4th July 2021) - Jones, Amy; Read, John; Wood, Lisa
Abstract: Background: Historically, the content of psychotic experiences has tended to be of little importance to biological psychiatry, with hallucinations and delusions being seen as symptoms of mental illness rather than meaningful experiences or responses to life circumstances. Aims: This study aims to explore the thematic content of psychotic phenomena in a sample of clients with a first episode of psychosis. Methods: The electronic medical records of 160 services users of two Early Intervention for Psychosis Services were comprehensively reviewed. A thematic analysis was used to explore the thematic content of psychotic symptoms recorded by healthcare professionals. Results: The results illustrate 30 themes and 85 sub-themes. This includes delusional beliefs (e.g. "being harmed, attacked or killed", "being monitored or followed by others", "special powers or abilities") and hallucinations (e.g. "commanding voice", "derogatory/critical voice", "commentary"). Conclusions: The results illustrate the extensive and varied experience of psychosis within this sample. Based on the findings of this study, it is hoped that future research studies and mental health services will attend to the meaning and content of psychotic experiences.